Analysis of Child Protection from Bullying at Muhammadiyah Elementary School 1 Candi Labschool UMSIDA: Analisis Perlindungan Anak dari Bullying di Sekolah Dasar Muhammadiyah 1 Candi Labschool UMSIDA - Arwiny, Siti Khoirotul; Amrullah, Muhlasin (Journal of Islamic and Muhammadiyah Studies, 2023)
This The purpose of this study was to anticipate bullying act in SD Muhammadiyah 1 Candi Labschool UMSIDA. To achieve that purpose, the researcher used qualitative research in the type of phenomenological research. The data collection techniques in the form of interviews, observation and documentation. The results of this study showed that the school have several school activities to anticipate bullying act, such as anti-violence programs, discussions, full supervision, gathering with students, creed/moral approaches, academic approaches, persuasive approaches, home visits, teacher training and parenting seminars. In anticipating the occurrence of bullying, school not only focus on student activities, but also provide understanding to parents and teachers to collaborated in anticipating bullying behavior in schools. Assistance for children with special needs (ABK) to avoid undesirable things when their child is in a tantrum.